Pilgrimage Tourism: A Study of Goshaikunda Lake of Nepal - Kuikel, Asmit (Scientific Researches in Academia, 2023)
Pilgrimage is spiritual tourism to receive heavenly blessings. The study focuses on pilgrimage tourism and its importance. The study highlights adventure tourism and pilgrimage tourism in the context of Nepal. The focus of the article is on the pilgrimage industry in Nepal's Goshaikunda Lake, one of the most revered bodies of water that Lord Mahadev is said to have created to get rid of the effect of poison named Kalkut. The importance of the festival and Goshaikunda in both the Hindu and non- Hindu communities is highlighted in the paper. The principal two ways to Goshaikunda Lake are through Dhunche and Sundarijal, both of which have similar importance and adventure, as well as geographical and natural beauty. The ideal trekking path from Langtang to Helambu has also been created around Goshaikunda Lake. They are also included in the Ramsar wetland list, along with all the lakes associated with it. The paper is qualitative, more descriptive, explanatory, and entirely based on the researchers' personal experience of visiting Goshaikunda Lake as a primary source of data and literature as a secondary source, both of which are collected and analyzed qualitatively